2022
DOI: 10.5530/pj.2022.14.128
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of DPPH, CUPRAC, and FRAP Methods, as well as Activity of Alpha-Glucosidase Inhibiting Enzymes from Tinospora crispa (L.) Stem Ultrasonic Extract

Abstract: Aims:The goal of this work was to get the stem extract of Tinospora crispa (L.) using ultrasoundassisted extraction (UAE) with duration and amplitude changes to achieve optimal extraction conditions. The antioxidant potential of the extract as measured by 2,2-diphenyl-1-picrylhydrazyl (DPPH), CUPRAC (Cupric Ion Reducing Antioxidant Capacity), FRAP (Ferric Reducing Ability of Plasma), and its antidiabetic potential. Results: The third test of antioxidant methods showed that the measurement of antioxidant activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 9 publications
0
4
0
1
Order By: Relevance
“…Ekstrak isolat M7 dan P1 memiliki aktivitas antioksidan yang berbeda yang diindikasikan oleh nilai IC50 yang bervariasi baik terhadap radikal DPPH maupun ABTS (Tabel 1). Berdasarkan nilai IC50-nya, aktivitas anitoksidan ekstrak bahan alam dapat digolongkan menjadi beberapa kategori, antara lain sangat kuat (<50 µg/mL), kuat (50-100 µg/mL), moderat (101-150 µg/mL), lemah (>150 µg/mL) (Irawan et al, 2022) Viabilitas sel MCF-7 menurun setelah diberi perlakuan ekstrak P1 dan M7 selama 48 jam. Ekstrak tersebut juga menginduksi terjadinya perubahan morfologi sel MCF-7 seperti adanya kerusakan membran dan apoptosis sel MCF-7, sehingga densitas MCF-7 yang diuji dengan ekstrak bakteri lebih rendah dibandingkan pada perlakuan tanpa ekstrak (Gambar 1).…”
Section: Aktivitas Antioksidan Ekstrak Bakteri Tanahunclassified
“…Ekstrak isolat M7 dan P1 memiliki aktivitas antioksidan yang berbeda yang diindikasikan oleh nilai IC50 yang bervariasi baik terhadap radikal DPPH maupun ABTS (Tabel 1). Berdasarkan nilai IC50-nya, aktivitas anitoksidan ekstrak bahan alam dapat digolongkan menjadi beberapa kategori, antara lain sangat kuat (<50 µg/mL), kuat (50-100 µg/mL), moderat (101-150 µg/mL), lemah (>150 µg/mL) (Irawan et al, 2022) Viabilitas sel MCF-7 menurun setelah diberi perlakuan ekstrak P1 dan M7 selama 48 jam. Ekstrak tersebut juga menginduksi terjadinya perubahan morfologi sel MCF-7 seperti adanya kerusakan membran dan apoptosis sel MCF-7, sehingga densitas MCF-7 yang diuji dengan ekstrak bakteri lebih rendah dibandingkan pada perlakuan tanpa ekstrak (Gambar 1).…”
Section: Aktivitas Antioksidan Ekstrak Bakteri Tanahunclassified
“…D2 extract exhibited antioxidant activity against two free radicals, including DPPH (IC50: 242.61±3.2 µg/mL) and ABTS (IC50: 317.32±9.3 µg/mL) (Table 4). According to its IC50 values (>150 µg/mL), D2 extract has weak antioxidant activity [19]. However, the antioxidant of D2 extract (extract derived from leaf endophytic bacteria from M. fatua) is still more active than leaf extract of the plant extracted with various organic solvents, which is ranging from 535-2,630 µg/mL [6].…”
Section: Antioxidant and Cytotoxic Properties Of D2 Extractmentioning
confidence: 99%
“…The standard curves of ascorbic acid (4 -20 mg/L) and Trolox (4 -12 mg/L) were used to determine the antioxidant capacity of the sample solution. FRAP was calculated against the dried extract [19,20].…”
Section: Antioxidant Capacity Assaymentioning
confidence: 99%
“…The standard curve of ascorbic acid (12 -40 mg/L) and Trolox (4 -12 mg/L) was used to determine the antioxidant capacity of the sample solution. CUPRAC was calculated against the dried extract [19,20]. The extraction yield indicated that the hot maceration had the maximum extraction efficiency (Tabel 1).…”
Section: Antioxidant Capacity Assaymentioning
confidence: 99%